Violencia acústica en los viajes en autobús (Intercom - Revista Brasileira de Ciências da Comunicação, 2023)
The article focuses on the recurring and conflicting case of musical performance on public transport, analyzing the forced musical experience as an act of violence entangled with several other forms of violence. It discusses how fear conditions the listening of musical experience in urban environments, shaped by shared values, ideas, and prejudices about music that is spread in public transport. The imposition of a certain musical repertoire on other passengers is configured as a political action that claims to be heard by individuals who suffer different types of oppression. However, at the same time, it contributes to the sedimentation of stigmatization reinforced by forced listening. Informed by interviews in Rio de Janeiro, the text seeks to deepen the debate on the uses of music in public spaces, incorporating the complexities and contradictions that permeate sound and musical control in public transport in Latin American metropolises.
Keywords: Música; Transporte público; Violencia; Espacio público; Juventud